Prognostic signature based on mitochondria- and angiogenesis-related genes associated with immune microenvironment of multiple myeloma - Dai Zhang; Yu Xing; Lu Liu; Xiaoqing Zhang; Cong Ma; MengYao Xu; Ruiqi Li; HanJing Wei; Yan Zhao; Bingxin Xu; Shuhao Mei (Hematology)
Introduction: Mitochondria and angiogenesis play key roles in multiple myeloma (MM) development, but their interrelated genes affecting MM prognosis are under-studied.Methods: We analyzed TCGA_MMRF and GSE4581 datasets to identify four genes – CCNB1, CDC25C, HSP90AA1, and PARP1 – that significantly correlate with MM prognosis, with high expression indicating poor outcomes.Results: A prognostic signature based on these genes stratified patients into high- and low-risk groups, with the latter showing better survival. The signature was validated as an independent prognostic factor. Biological function analysis revealed differences in cell cycle processes between risk groups, and immune microenvironment analysis showed distinct immune cell infiltration patterns.Conclusion: This mitochondria- and angiogenesis-related prognostic signature could enhance MM prognosis assessment and offer new therapeutic insights.